2008
DOI: 10.1029/2008gb003274
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon evidence for the importance of surface vegetation on fermentation and methanogenesis in contrasting types of boreal peatlands

Abstract: [1] We found a consistent distribution pattern for radiocarbon in dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and methane replicated across spatial and temporal scales in northern peatlands from Minnesota to Alaska. The 14 C content of DOC is relatively modern throughout the peat column, to depths of 3 m. In sedge-dominated peatlands, the 14 C contents of the products of respiration, CH 4 and DIC, are essentially the same and are similar to that of DOC. In Sphagnum-and woody plant-dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
156
3
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(172 citation statements)
references
References 84 publications
10
156
3
2
Order By: Relevance
“…Whereas the solid-phase peat represents an important substrate for decomposition, a large proportion of CH 4 and CO 2 production uses materials in the dissolved phase (39). This is particularly true in fens due to fen DOM's high lability (relative to bog DOM), such that the majority of fen respiration products is derived from DOM decomposition (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the solid-phase peat represents an important substrate for decomposition, a large proportion of CH 4 and CO 2 production uses materials in the dissolved phase (39). This is particularly true in fens due to fen DOM's high lability (relative to bog DOM), such that the majority of fen respiration products is derived from DOM decomposition (39).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true in fens due to fen DOM's high lability (relative to bog DOM), such that the majority of fen respiration products is derived from DOM decomposition (39). We therefore analyzed DOM chemistry and reactivity in addition to peat chemistry and reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of dissolved gases in peatlands have shown the CO 2 component to be older (Charman et al 1994), younger (Charman et al 1999), or essentially the same age (Aravena et al 1993;Chanton et al 2008) as the CH 4 component of dissolved gases. Our results are in agreement with the latter 2 studies in that the CO 2 component was either slightly younger, or the same age as the CH 4 component collected from the same depth.…”
Section: Field Experiments -Comparison With Other Studiesmentioning
confidence: 99%
“…This extra carbon cannot have been derived from dissolved organic carbon (DOC), which has been identified as one of the forms of carbon that may be transported in the peat profile (e.g. Aravena et al 1993), and is clearly a source for gases in peatlands (Chanton et al 2008), because although this process would lead to peat gases younger in age than the surrounding peat, it would not lead to CO 2 being younger than CH 4 at the same depth.…”
Section: Field Experiments -Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation